Determinant Factors in the Implementation of Information Technology Strategic Management to Academicians' Performance in Higher Education Institution - Cepy Slamet; Aedah binti Abdul Rahman; Muhammad Ali Ramdhani (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2021)
This study aimed to understand the determinant factors of information technology (IT) strategic management to individual (lecturer) performance using data samples from selected higher education institutions in Indonesia. Since the use of IT innovation in (HEI) is often considered a lens representing the strength of strategy, competitiveness, and quality within a corporate view, it is vague on its impact on individual performance. The investigation included data collection based on an online survey conducted on 325 respondents to investigate the relationship between strategic factors, elaborated into several relevant criteria. The results of statistical data processing showed that of all the strategic factors involved, the business model and strategic alignment categorized in high determinations in influencing academicians' performance at HEI.